Effects of Controlling the AZO Thin Film's Optical Band Gap on AZO/MEH-PPV Devices with Buffer Layer - Jaehyoung Park; Ki-Chang Jung; Ari Lee; Hyojung Bae; Daehwa Mun; Jun-Seok Ha; Young-Bu Mun; E. M. Han; Hang-Ju Ko (International Journal of Photoenergy)
Organic/inorganic hybrid solar cells were fabricated incorporating aluminum-doped zinc oxide (AZO) thin films of varying optical band gap in AZO/poly(2-methoxy-5-(2′-ethyl-hexyloxy)-p-phenylene vinylene) structures. The band gaps were controlled by varying the flow rates of Ar and O2 used to deposit the AZO. Devices with CdS buffer layer were also fabricated for improved efficiency. The effects of AZO optical band gap were assessed by testing the I–V characteristics of devices with structures of glass/ITO/AZO/MEH-PPV/Ag under AM1.5 illumination (100 mW/cm2). Efficiency was improved about 30 times by decreasing the AZO optical band gap, except in devices deposited without oxygen. A power conversion efficiency of 0.102% was obtained with the incorporation of a CdS buffer layer.